2019
DOI: 10.3389/fnhum.2019.00054
|View full text |Cite
|
Sign up to set email alerts
|

Linking Emotional Reactivity Between Laboratory Tasks and Immersive Environments Using Behavior and Physiology

Abstract: An event or experience can induce different emotional responses between individuals, including strong variability based on task parameters or environmental context. Physiological correlates of emotional reactivity, as well as related constructs of stress and anxiety, have been found across many physiological metrics, including heart rate and brain activity. However, the interdependances and interactions across contexts and between physiological systems are not well understood. Here, we recruited military and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…However, what should be noted is that the emotion-cognition relation has been mainly explored within a controlled laboratory setting where emotion invoking stimuli were exposed very briefly. It is still unclear regarding how well stationary laboratory behavior predicts task performance when the stimuli have features more typical of real-world environments (Pavlenko, 2008;Roy et al, 2019). Therefore, the potential differences between laboratory settings and real environments call for further research to address the effects of real emotional contexts on lexical processing.…”
Section: Research Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…However, what should be noted is that the emotion-cognition relation has been mainly explored within a controlled laboratory setting where emotion invoking stimuli were exposed very briefly. It is still unclear regarding how well stationary laboratory behavior predicts task performance when the stimuli have features more typical of real-world environments (Pavlenko, 2008;Roy et al, 2019). Therefore, the potential differences between laboratory settings and real environments call for further research to address the effects of real emotional contexts on lexical processing.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Virtual reality digital technology can enable its users to be immersed in a 3D virtual environment, and accordingly activate active interaction between the simulated reality and users. Virtual reality can also allow for the use of multiple senses that function simultaneously during information processing (Roy et al, 2019). In a VR context, the addition of living objects such as virtual people or animals can more realistically imitate the real world, so users could have a virtual sense of immersion (Fisher and Fraser, 1998).…”
Section: Virtual Reality Simulated Scenarios and Galvanic Skin Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The EEG data will be in a separate manuscript. Studies have reported that HRV is significantly correlated both with negative symptoms [21] and with frontoparietal network connectivity [22,23]. Here, we report the methods of collecting and analyzing the data of HRV.…”
Section: Biological Markersmentioning
confidence: 99%
“…Participants used the numeric keypad on the keyboard to rate their emotional intensity in response to each image, for a total of 60 images, on a scale ranging from 1 (low emotional intensity) to 9 (high emotional intensity). Experimental timelines for these tasks are shown in Figure 1A and further details can be found in reference [39].…”
Section: Experimental Designmentioning
confidence: 99%